Antioxidant, Antibacterial, and Anticancer Activities of Bitter Gourd Fruit Extracts at Three Different Cultivation Stages. (23rd April 2020) - Naqvi, Syed Ali Raza; Ali, Shafaqat; Sherazi, Tauqir A.; Haq, Atta-Ul; Saeed, Muhammad; Sulman, Muhammad; Rizwan, Muhammad; Alkahtani, Saad; Abdel-Daim, Mohamed M.
Abstract : In this study, we are presenting the effect of three ripening stages of air-dried bitter gourd fruit extracts on phenolic acid composition, antioxidant, antibacterial, and anticancer activities. The results showed mature bitter gourd fruit extract in 100% methanol showing 78% DPPHº scavenging activity. Immature dried fruit extract in 80% and 100% methanol showed promising antibacterial activities, i.e., >18.5 ± 0.21 mm zone-of-inhibition against Staphylococcus aureus, while mature dried fruit extract in 80% methanol showed 18.4 ± 0.17 mm zone-of-inhibition against Escherichia coli . Anticancer activity results of 100% methanol extracts of ripened fruit possess showed 6.72 ± 1.81 and 3.55 ± 0.51 mg/mL IC50 values with HeLa and MDBK cancer cell lines, respectively. The overall results indicate that the immature and ripen fruits of BG could be extracted in pure methanol as an antibacterial and anticancer phytomedicine.